The characterisation of carbapenem-resistant Acinetobacter baumannii and Klebsiella pneumoniae in a teaching hospital in Malaysia - Lau, Min Yi; Ponnampalavanar, Sasheela; Chong, Chun Wie; Dwiyanto, Jacky; Lee, Yee Qing; Woon, Jia Jie; Kong, Zhi Xian; Jasni, Azmiza Syawani; Lee, Michelle Chin Chin; Obaidellah, Unaizah Hanum; Teh, Cindy Shuan Ju (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Background/Objectives: The emergence and dissemination of carbapenem-resistant organisms, particularly Acinetobacter baumannii and Klebsiella pneumoniae, pose a significant threat to healthcare systems worldwide. This retrospective study aims to characterise carbapenem-resistant Acinetobacter baumannii (CRAB) and carbapenem-resistant Klebsiella pneumoniae (CRKP) strains in a teaching hospital and to determine the risk factors associated with patients’ in-hospital mortality. Methods: A total of 90 CRAB and 63 CRKP were included in this study. Carbapenemase genes and MLST types of CRAB and CRKP were determined using specific primers. Risk factors associated with in-hospital mortality were analysed with collected data. Results: All the CRAB strains consisted of OXA carbapenemase genes, with 98% of the strains co-harbouring blaOXA-23-like and blaOXA-51-like carbapenemase genes. Conversely, blaNDM is the predominant carbapenemase gene in CRKP, followed by blaOXA-48-like carbapenemase genes. ST2 and ST20 are the dominant MLST types in CRAB and CRKP, respectively. In CRAB, multivariate analysis identified age, ethnicity, the presence of a mechanical ventilator, and patients who experienced previous exposure to clindamycin in the last 90 days as associated with an increased risk of in-hospital mortality. In contrast, older age, male, ICU admission, and the presence of an indwelling urinary catheter were significantly associated with an increased risk of mortality for patients with CRKP. Conclusions: Both CRAB and CRKP lead to high rates of mortality. The MLST profile showed that the genomic patterns of CRKP were highly diverse, whereas CRAB strains had low genetic diversity. To tackle these challenging pathogens, robust surveillance and an in-depth understanding of molecular epidemiology and genomics studies are needed to tailor infection control strategies and individualise treatment approaches.